Civil Society Nagari Minangkabau: Restrukturisasi Adat dalam Lintasan Kebijakan - Aulia Rahmat (Bakaba, 2019)
The hegemony between religious and ethnic identities that are part of cultural rights and community rights to identity. Later both of these exponents then came into contact with the concepts of modernization and globalization, even the civil society. Nagari as the crystallization of the cultural rights of the Minangkabau’s indigenious people on the history of Indoesian government always changes. This study uses a grounded research approach with constant comparacy analysis. A series of changes that occurred did not eliminate the existence of modeling civil society that is different from the western concept. This can be seen in the nagari governance model in regulation.